2019
DOI: 10.1016/j.jstrokecerebrovasdis.2019.104375
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Reduces Inflammatory Brain Injury after Subarachnoid Hemorrhage: Involvement of PI3K/Akt Pathway

Abstract: Background: Our previous study showed that propofol, one of the widely used anesthetic agents, can attenuate subarachnoid hemorrhage (SAH)-induced early brain injury (EBI) via inhibiting inflammatory and oxidative reaction. However, it is perplexing whether propofol attenuates inflammatory and oxidative reaction through modulating PI3K/Akt pathway. The present study investigated whether PI3K/Akt pathway is involved in propofol's anti-inflammation, antioxidation, and neuroprotection against SAH-induced EBI. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Numerous studies have indicated that the PI3K/AKT signaling pathway is an important intracellular signaling pathway that plays a role in a variety of cellular physiological processes, including cell proliferation, cell apoptosis and inflammatory response (25)(26)(27). Chang et al reported that 7-ketocholesterol contributed to thrombosis via the induction of endothelial damage, apoptosis and inflammatory responses, which were associated with the activation of PI3K/AKT signaling (28).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that the PI3K/AKT signaling pathway is an important intracellular signaling pathway that plays a role in a variety of cellular physiological processes, including cell proliferation, cell apoptosis and inflammatory response (25)(26)(27). Chang et al reported that 7-ketocholesterol contributed to thrombosis via the induction of endothelial damage, apoptosis and inflammatory responses, which were associated with the activation of PI3K/AKT signaling (28).…”
Section: Discussionmentioning
confidence: 99%
“…Sugawara et al [38] found that intraperitoneal injection of simvastatin reduced nerve dysfunction and cerebral vasospasm in SAH rats, and intravenous injection of wortmannin (PI3K/Akt inhibitor) abolished the neuroprotective effects of simvastatin, which indicated that the PI3K/Akt signaling pathway is involved in the neuroprotective effect of cerebral vasospasm after SAH. Zhang HB et al [39] demonstrated that propofol attenuates SAHinduced EBI by inhibiting in ammation and oxidative stress, which was reversed by LY294002 (PI3K/Akt inhibitor) administration. Furthermore, broblast growth factor-2 alleviated neurological impairments, brain edema, and neuronal apoptosis following SAH.…”
Section: Discussionmentioning
confidence: 99%
“…A follow up study by the same authors showed that intraperitoneal administration of propofol 50 mg/kg at 2 h and repeated at 12 h after SAH in a rat endovascular perforation model reduced cerebral edema, blood–brain barrier permeability and improved neurological scores. Propofol’s EBI protection in this study was reversed by LY294002, a specific inhibitor of Phosphatidylinositol 3-kinase/Akt (PI3K/Akt) signaling pathway, suggesting a possible involvement of PI3K/Akt pathway in propofol’s protection [ 19 ].…”
Section: Anesthetics/adjuvants In Ebi After Sahmentioning
confidence: 99%
“…Available experimental and clinical evidence, though somewhat limited in scope, have shown that propofol protects against SAH-induced EBI [ 18 , 19 ]. Whether propofol provides protection against SAH-induced DCI, however, remains unclear.…”
Section: Summary Of Anesthetics/adjuvants and Neurovascular Protection In Sahmentioning
confidence: 99%